Mechanism of action and therapeutic targeting of CD30 molecule in lymphomas - Li, Zhaoxia; Guo, Wei; Bai, Ou (Frontiers in Oncology, 2023)
At present, the treatment of lymphoma has entered the era of precision medicine, and CD30, as a transmembrane protein, has become an important marker to help the diagnosis and formulation of treatment plans for lymphomas. This protein is widely expressed in various types of lymphomas and can play a role through nuclear factor-κB (NF-κB), mitogen-activated protein kinase (MAPK), and other pathways, and ultimately lead to the up-regulation of CD30 expression to give tumor cells a survival advantage. Brentuximab vedotin (BV), as an antibody-drug conjugate (ADC) targeting CD30, is one of the first new drugs to significantly improve survival in patients with CD30+lymphomas. However, the biological function of CD30 has not been fully elucidated. Therefore, this review highlights the CD30-mediated tumor-promoting mechanisms and the molecular factors that regulate CD30 expression. We hope that a better understanding of CD30 biology will provide new insights into clinical treatment and improve the survival and quality of life of lymphoma patients.